A square-triangular number is a perfect square that is also a triangular number . The first three square-triangular numbers are 0, 1, and 36.
What is the 6 th square-triangular number?
Note:
For example,
0
2
=
0
,
1
2
=
1
,
2
2
=
4
,
3
2
=
9
,
.
.
.
are perfect squares and
0
,
1
,
1
+
2
=
3
,
1
+
2
+
3
=
6
,
.
.
.
are triangular numbers.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Were looking for a pair of natural numbers ( a , b ) such that a 2 = 2 b ( b + 1 ) In order to apply Vieta root-jumping , we'll make a = b − k . Substituting and reorganizing, we have b 2 − 4 b k − b + 2 k 2 = 0 If we have a solution ( b 1 , k 1 ) we can fix b = b 1 , which gives us 2 k 2 − ( 4 b 1 ) k + ( b 1 2 − b 1 ) = 0 And from Vieta's formula applied to the constant term, we know that if k 1 is an integer solution, then there exists another integer solution k 2 such that k 2 = 2 k 1 b 1 2 − b 1 In an analogous procedure, fixing k = k 2 , and reorganizing the equation so it becomes a polinomyal in b, we will find soluutions b 1 (which we already found earlier) and b 2 such that b 2 = b 1 2 k 2 2 Now, the reason we first fixed b = b 1 instead of k = k 1 is we want to get greater and greater solutions, by fixing b = b 1 first, we would end up at the solution b = 0 , k = 0 , you can try it for yourself and check it.
For the same reason, the "intermediate" solution ( b 1 , k 2 ) doesn't work for us, because k 2 − b 1 = b 1 − k 1 , and remember, a = b − k .
Both previous statements seem a bit out of the blue, but they become obvious if you graph 2 y 2 − ( 4 x ) y + ( x 2 − x ) = 0 along with y = x and look at where these solutions are, remember: vieta jumping finds solutions by jumping in 9 0 o angles between the hyperbola's "arms".
Summarizing what we've done: if we have a solution ( b 1 , k 1 ) , we can find another solution ( b 2 , k 2 ) , where b 2 and k 2 are given by the expressions discussed earlier. Now, we can put b 3 = 8 and k 3 = 2 and jump between the solutions until we get to ( b 6 , k 6 ) . I've done this and organized the values found in this table:
n | b n | k n |
1 | 0 | 0 |
2 | 1 | 0 |
3 | 8 | 2 |
4 | 49 | 14 |
5 | 288 | 84 |
6 | 1681 | 492 |
Finally, the number we want is ( b 6 − k 6 ) 2 which is 1 1 8 9 2 which is
1413721 |
For the same reason, the "intermediate" solution ( b 1 , k 2 ) doesn't work for us, because k 2 − b 1 = b 1 − k 1 , and remember, a = b − k .
I think this statement needs clarification:
From 2 k 2 − ( 4 b ) k + ( b 2 − b ) = 0 We can conclude that 2 b 1 = 2 k 2 k 1 2 + b 1 2 + b 1 Which is exactly the same thing you'd get by adding k 1 with the expression for k 2 . Therefore, k 1 + k 2 = 2 b 1 The rest is simple algebra
Problem Loading...
Note Loading...
Set Loading...
We want 2 1 n ( n + 1 ) = m 2 , and this equation becomes ( 2 n + 1 ) 2 − 2 ( 2 m ) 2 = 1 The non-negative integer solutions of Pell's equation x 2 − 2 y 2 = 1 are obtained by the formula x k + y k 2 = ( 1 + 2 ) 2 k = ( 3 + 2 2 ) k for all k ≥ 0 . Note that x k will always be odd, and y k will always be even. With x 5 = 3 3 6 3 and y 5 = 2 3 7 8 we obtain n = 1 6 8 1 and m = 1 1 8 9 , making the answer 2 1 n ( n + 1 ) = 1 4 1 3 7 2 1